Profit efficiency of banks in Colombia with undesirable output: A directional distance function approach - Camilo Almanza Ramírez; Jhon James Mora; Andrés Cendales (Kiel Institute for the World Economy (IfW), 2017)
This study investigates the sources of bank efficiency in Colombia over the period 2000-2011. To perform this research, the authors propose a score of bank efficiency using the directional distance function, which was estimated using data envelopment analysis. Additionally, they use an ordered probit panel regression to explore the effects of some market-related and bank-specific factors on efficiency. The authors' results show that the non-inclusion of non-performing loans (NPLs) leads to higher bank inefficiency indicators, which are significantly different from those obtained when NPLs are included. Further, the authors find that economic growth, capital risk, foreign and national banks, and account liquidity risk explain, in part, the efficiency of Colombian banks.
Keywords: D22; G21; 330; data envelopment analysis; Colombia; directional distance function; nonperforming loans; ordered probit panel models